Vendor Lock Analysis In Subsurface Data Management In Xyz Organization And Its Impact On State Data Sovereignty - Zulfikar Zulfikar; Mohammad Achmad Amin Soetomo; Soebowo Musa (Syntax Corporation, 2022)
Vendor lock-in is a situation where users of a product depend on one provider and cannot switch to another provider without large costs and a long time (Opara-Martins, Sahandi, & Tian, 2016). So, there is a potential monopoly that can be done by vendors. Oil and gas data processing in the XYZ Organization, especially for subsurface data processing, tends to lead to vendor lock practices where the management of subsurface data is very dependent on the application used at this time, the data used is not open and applies internationally so that there is a vendor lock where the processed data cannot be used after the expiration date. It is also at risk of data ownership where XYZ organization and other institutions cannot easily process the data because the standard data used is limited to the applications currently used. The vendor lock has the potential to disrupt state data sovereignty because the control of data processing only depends on certain vendors.